2019
DOI: 10.1039/c9na00217k
|View full text |Cite
|
Sign up to set email alerts
|

A new nanowire-based lithium hexaoxotungstate anode for lithium-ion batteries

Abstract: This study reports one dimensional lithium hexaoxotungstate (Li6WO6), with a diameter in the range of 200–500 nm, as a novel anode material for lithium-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…These secondary lithium tungstate products (Li x WO y ) were also reported as active materials with high lithium-ion conductivities, as demonstrated in previous studies. , We, thus, concluded that the Li x WO y phases underwent conversion by the end of charging. The conversion energies of Li x WO y phases E (cv2) and E (cv3) were estimated as follows: Estimated values of E (cv2) and E (cv3) were 1.1 and 1.0 eV, and these implied the existence of the conversion potential lower than that of WO 3 . To observe lithiation in the WO 3 -NRs and experimentally prove the theoretically descripted charging mechanism, we performed an in situ TEM experiment.…”
Section: Results and Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These secondary lithium tungstate products (Li x WO y ) were also reported as active materials with high lithium-ion conductivities, as demonstrated in previous studies. , We, thus, concluded that the Li x WO y phases underwent conversion by the end of charging. The conversion energies of Li x WO y phases E (cv2) and E (cv3) were estimated as follows: Estimated values of E (cv2) and E (cv3) were 1.1 and 1.0 eV, and these implied the existence of the conversion potential lower than that of WO 3 . To observe lithiation in the WO 3 -NRs and experimentally prove the theoretically descripted charging mechanism, we performed an in situ TEM experiment.…”
Section: Results and Discussionsupporting
confidence: 79%
“…These secondary lithium tungstate products (Li x WO y ) were also reported as active materials with high lithium-ion conductivities, 65 as demonstrated in previous studies. 66,67 We, thus, concluded that the Li x WO y phases underwent conversion by the end of charging. The conversion energies of Li x WO y phases E(cv2) and E(cv3) were estimated as follows:…”
Section: Resultsmentioning
confidence: 88%
“…[1][2][3][4][5] Recently, the electronic properties of nanomaterials have been investigated to develop new alternative energy sources which are friendly with the environment, such as fuel cells, photocells; as well as energy storage devices (supercapacitors and batteries). 3,[6][7][8][9][10][11][12][13][14][15][16] Nowadays, one of the most efficient energy-storage devices are the lithium batteries, whose development started in parallel with the sodium ones in the 1970's. [17][18][19] Li and Na ions batteries are very similar, but the former have been incorporated in many electronic devices due to the lighter weight and smaller atomic radius of Li atoms in comparison with the Na ones.…”
Section: Introductionmentioning
confidence: 99%
“…28 Since delithiation is the removal of a lithium ion and results in an increase in catalytic performance, no report on the presence of excess lithium for the water oxidation reaction is reported. 29 Inspired by recent work in the field of delithiated LiMn 2 O 4 prompted us to study Li-rich Li 4 Mn 5 O 12 based oxide for water oxidation activity. Li 4 Mn 5 O 12 is a Li-rich spinel where 1/6th of the Mn of LiMn 2 O 4 is replaced by Li.…”
Section: Introductionmentioning
confidence: 99%
“…28 Since delithiation is the removal of a lithium ion and results in an increase in catalytic performance, no report on the presence of excess lithium for the water oxidation reaction is reported. 29…”
Section: Introductionmentioning
confidence: 99%